Pengaruh Insentif Terhadap Produktivitas Kerja Karyawan Pada Pabrik Kopi Cap Gajah Di Rangkasbitung - Yumhi .; Rendi Dwi Rahmat; Hurriyah Agustini; Bambang Pujo Purwoko (E-Journal Studia Manajemen, 2014)
An incentive is one very good way applied to direct employees at the company's goals. Incentive is seen as one of the elements that can affect employee productivity. The purpose of this study was to analyze the effect of incentives on work productivity. This study uses a method used by this author is a quantitative method. The sampling technique using saturated sample of 40 respondents. Results of this study are: There is a positive and significant impact on performance incentives.